Neither episodic, nor destined to failure? The endurance of Hungarian populism after 2010. Issue 6 (18th August 2019) - Csehi, Robert
ABSTRACT: How can populists potentially extend their time in power? Departing from the notion that populism is a "thin-centered" ideology, the article argues that as long as populists manage to continuously (a) reconstruct "the elite" and "the people, " (b) reinforce the antagonistic relationship between "the corrupt elite" and "the pure people, " and (c) remodel popular sovereignty, it is likely that they can lengthen the life expectancy of their regime. Analyzing the case of Hungary starting in 2010, the article demonstrates that Prime Minister, Viktor Orbán was successful with respect to this "three-course approach." He managed to reconstruct "the elite" from "representatives of the past" to a "homo sorosensus, " and widened the scope of "the people" from "we, Hungarians" to "we, the sovereign nations." Similarly, Orbán renewed the conflict between the ever changing elite and "the people, " turning from economic-driven to identity politics. Finally, Orbán reinvented a toolkit of new, innovative measures that reflected a preference for greater popular sovereignty. The article builds on an analysis of Orbán's selected speeches and corresponding political and legal measures initiated by the regime that formed an integrative part of the "three-course approach" in Hungary.